2021
DOI: 10.3233/wor-213456
|View full text |Cite
|
Sign up to set email alerts
|

Analyses and anticipating the future trend of accidents in an electricity distribution company of Iran: A time series analysis

Abstract: BACKGROUND: Many work-related fatalities happen every year in electricity distribution companies. This study was conducted to model accidents using the time series analysis and survey descriptive factors of injuries in an electricity distribution company in Tehran, Iran. METHODS: Data related to 2010 to 2017 were collected from the database of the safety department. Time Series and trend analysis were used for data analyzing and anticipating the accidents up to 2022. RESULT: Most of the accidents occurred in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Workers’ negligence was the cause of 75% of deaths. Also, their findings indicated that occupational injuries are going to have an increase in the future [ 34 ]. These findings show the need to use risk assessment methods appropriate to the nature of this industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workers’ negligence was the cause of 75% of deaths. Also, their findings indicated that occupational injuries are going to have an increase in the future [ 34 ]. These findings show the need to use risk assessment methods appropriate to the nature of this industry.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different industries of electricity production, distribution and consumption, the electricity distribution industry is prone to more occupational safety risks due to the direct exposure of employees to power lines and electricity sources. Various incidents and accidents occur in the distribution sector of the electricity industry and cause numerous human and financial losses every year [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, management experts and organizational psychologists pay attention to the factors that affect the increase or decrease of human efficiency, and try to increase the impact of effective factors and reduce the role of negative factors by identifying these factors and applying the necessary measures (1). The International Labor Organization es-timates that there are 270 million occupational accidents in the world each year, resulting in the absences of more than three working days and 210,000 mortalities in the workplace (2). The cost of these injuries is so high that in the UK, the total cost of workplace injuries to employers in 2005 -2006 was estimated at around 1.2 -1.3 billion pounds (3).…”
Section: Introductionmentioning
confidence: 99%